2023
DOI: 10.3389/fpls.2023.1276472
|View full text |Cite
|
Sign up to set email alerts
|

Microbe-associated molecular pattern recognition receptors have little effect on endophytic Arabidopsis thaliana microbiome assembly in the field

Caroline Oldstone-Jackson,
Feng Huang,
Joy Bergelson

Abstract: Plant microbiome structure affects plant health and productivity. A limited subset of environmental microbes successfully establishes within plant tissues, but the forces underlying this selectivity remain poorly characterized. Transmembrane pattern recognition receptors (PRRs), used by plants to detect microbe-associated molecular patterns (MAMPs), are strong candidates for achieving this selectivity because PRRs can potentially interact with many members of the microbiome. Indeed, MAMPs found in many microbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 126 publications
0
1
0
Order By: Relevance
“…The intricate function of plant innate immune pathways in controlling the endophyte community may be influenced by a range of pleiotropic factors. It is suggested that the signaling pathway triggered via the single recognition of microbe-associated molecular patterns (MAMPs) through their perception by pattern recognition receptors (PRRs) might not significantly impact the composition of the plant endophytic microbiome, yet represents only one aspect of the multi-level interactions between plant innate immune systems and endophytes [127]. It was found that in Arabidopsis, pattern-triggered immunity (PTI) and the MIN7 vesicle-trafficking pathway are involved in shaping the endophytic microbial community in the phyllosphere, and constitutively activated cell death 1 (CAD1) could be a potential convergent component of PTI and the MIN7 vesicle-trafficking pathway [128].…”
Section: Innate Immune Pathways In Plantsmentioning
confidence: 99%
“…The intricate function of plant innate immune pathways in controlling the endophyte community may be influenced by a range of pleiotropic factors. It is suggested that the signaling pathway triggered via the single recognition of microbe-associated molecular patterns (MAMPs) through their perception by pattern recognition receptors (PRRs) might not significantly impact the composition of the plant endophytic microbiome, yet represents only one aspect of the multi-level interactions between plant innate immune systems and endophytes [127]. It was found that in Arabidopsis, pattern-triggered immunity (PTI) and the MIN7 vesicle-trafficking pathway are involved in shaping the endophytic microbial community in the phyllosphere, and constitutively activated cell death 1 (CAD1) could be a potential convergent component of PTI and the MIN7 vesicle-trafficking pathway [128].…”
Section: Innate Immune Pathways In Plantsmentioning
confidence: 99%